Cancer incidence in cohorts of workers in the rubber manufacturing industry first employed since 1975 in the UK and Sweden. Issue 6 (6th January 2017) - Boniol, M; Koechlin, A; Sorahan, T; Jakobsson, K; Boyle, P
Abstract : Objectives: Increased cancer risks have been reported among workers in the rubber manufacturing industry employed before the 1960s, but it is unclear for workers hired subsequently. The present study focused on cancer incidence among rubber workers first employed after 1975 in Sweden and the UK. Methods: Two cohorts of rubber workers employed for at least 1 year were analysed. Standardised incidence ratios (SIRs), based on country-specific and period-specific incidence rates, were analysed for all cancers combined (except non-melanoma skin), bladder, lung, stomach cancer, leukaemia, non-Hodgkin's lymphoma and multiple myeloma. Exploratory analyses were conducted for other cancers with a minimum of 10 cases in both genders combined. Results: 16 026 individuals (12 441 men; 3585 women) contributed to 397 975 person-years of observation, with 846 cancers observed overall (437 in the UK, 409 in Sweden). No statistically significant increased risk was observed for any site of cancer. A reduced risk was evident for all cancers combined (SIR=0.83, 95% CI (0.74 to 0.92)), lung cancer (SIR=0.74, 95% CI (0.59 to 0.93)), non-Hodgkin's lymphoma (SIR=0.67, 95% CI (0.45 to 1.00)) and prostate cancer (SIR=0.77, 95% CI (0.64 to 0.92)). For stomach cancer and multiple myeloma, SIRs were 0.93 (95% CI (0.61 to 1.43)) and 0.92 (95% CI 0.44 to 1.91), respectively. No increased risk of bladder cancer was observed (SIR=0.88, 95% CI (0.61 to 1.28)). Conclusions: No significantly increased risk of cancer incidence was observed in the combined cohort of rubber workers first employed since 1975. Continued surveillance of the present cohorts is required to confirm absence of long-term risk and confirmatory findings from other cohorts would be important.